Inflammatory indices in meconium aspiration syndrome. Issue 6 (10th December 2015) - Hofer, Nora; Jank, Katharina; Strenger, Volker; Pansy, Jasmin; Resch, Bernhard
Summary: Introduction: Meconium aspiration syndrome (MAS) is linked to inflammation, but data on the patterns of hematological indices and C‐reactive protein (CRP) in MAS are lacking. The aim of the study was to evaluate CRP, white blood cell count (WBC), absolute neutrophil count (ANC), and immature‐to‐total neutrophil ratio (IT‐ratio) in MAS and to assess their association with disease severity. Methods: Retrospective cross‐sectional study including 239 consecutively admitted neonates with MAS to a level III NICU. Neonates with early onset sepsis were excluded. Results Neonates with severe MAS (invasive mechanical ventilation for <7 days) and very severe MAS (invasive mechanical ventilation for ≥7 days or high frequency ventilation or ECMO) had higher CRP and IT‐ratio compared to neonates with non‐severe MAS (no invasive mechanical ventilation) during the first 2 days of life (CRP: 13.0 and 40.9 vs. 9.5 mg/L, P  = 0.039 and <0.001, respectively) and neonates with very severe MAS had lower WBC and ANC. All four inflammatory indices correlated significantly with duration of invasive mechanical ventilation, duration of respiratory support and with length of hospital stay, arterial hypotension, and persistent pulmonary hypertension. Neonates with all four inflammatory indices beyond the normal range had a more than 20‐fold increase in risk for very severe MAS. Conclusion: High CRP and IT‐ratio and low WBC and ANC values were closely linked to a more severe course of MAS during the early phases of the disease. These findings reflect the role of inflammation in the pathogenesis of MAS.Pediatr Pulmonol. 2016;51:601–606 . 2015 Wiley Periodicals, Inc.